Removal of Hydrocarbon from Produced Water by Phytoremediation Method, Using Water Hyacinth (Eichhornia Crassipes) - Ehi Oria-Usifo; Isaac Enuma; Idonije Edward; David Okafor; Boluwade Segun; Uchenna Ukpai; Abraham Ajayi (International Journal of Scientific Research in Civil Engineering, 2025)
The Niger Delta region faces significant environmental challenges due to the discharge of untreated or inadequately treated produced water from oil exploration activities. This study investigates the potential of water hyacinth (Eichhornia crassipes) as a phytoremediation agent to remove hydrocarbons and improve the quality of produced water. Produced water samples were collected from the Obagi Flow Station in Rivers State, Nigeria, and subjected to treatment with water hyacinth under controlled laboratory conditions. Key parameters such as Biological Oxygen Demand (BOD), Total Dissolved Solids (TDS), and Total Petroleum Hydrocarbons (TPH) were monitored over 35 days. The results demonstrated significant reductions in pollutant concentrations: BOD levels decreased by 71.3%, TDS by 76.5%, and TPH by 98.9%. These reductions were attributed to the plant's extensive root system, which facilitates pollutant absorption and microbial activity in the rhizosphere. The study highlights the scalability, cost-effectiveness, and environmental sustainability of phytoremediation, particularly in resource-constrained regions. This research underscores the potential of water hyacinth as a viable alternative to conventional produced water treatment methods, offering a sustainable approach to mitigating hydrocarbon pollution and protecting aquatic ecosystems in oil-producing areas. Recommendations include integrating phytoremediation with existing treatment systems and further exploring biomass utilization post-remediation to enhance the economic viability of this method.
Keywords: Produced Water; Phytoremediation; Water Hyacinth; Hydrocarbon Removal; Environmental Pollution; Niger Delta